1973
DOI: 10.3758/bf03334432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Δ9-tetrahydrocannabinol on delayed matching-to-sample choice speeds in chimpanzees

Abstract: The effects of A 9 -THC on choice response speeds in chimpanzee short-term recognition memory were assessed in a delayed matching-to-sample task. Choice speeds were faster on correct than on incorrect trials and were inversely related to delay length. Although A 9 -THC lowered matching accuracy, it did not affect any aspect of choice speed, These results were interpreted as indicating that the disruption of short-term recognition memory produced by A 9 -THC reflects changes in acquisition-storage processes rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Increased choice RT as a function of delay supports earlier findings with nonoperated monkeys (Grilly & Ferraro, 1973;Jarrard & Moise, 1971). From results obtained with human subjects in short-term memory tasks, Murdock (1968) and Sternberg (1969) suggested that response latency may be a function of attention or retrieval processes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Increased choice RT as a function of delay supports earlier findings with nonoperated monkeys (Grilly & Ferraro, 1973;Jarrard & Moise, 1971). From results obtained with human subjects in short-term memory tasks, Murdock (1968) and Sternberg (1969) suggested that response latency may be a function of attention or retrieval processes.…”
Section: Discussionsupporting
confidence: 85%
“…From results obtained with human subjects in short-term memory tasks, Murdock (1968) and Sternberg (1969) suggested that response latency may be a function of attention or retrieval processes. A similar interpretation in the DMS task has led some investigators to suggest that attention and retrieval decrease as a function of the delay interval (Grilly & Ferraro, 1973;Jarrard & Moise, 1971). Therefore, the finding that choice RT was prolonged by FC may be due to an impairment of attention, retrieval, or both.…”
Section: Discussionmentioning
confidence: 77%